2014
DOI: 10.2147/ijn.s56298
|View full text |Cite
|
Sign up to set email alerts
|

Potential proinflammatory effects of hydroxyapatite nanoparticles on endothelial cells in a monocyte–endothelial cell coculture model

Abstract: Currently, synthetic hydroxyapatite nanoparticles (HANPs) are used in nanomedicine fields. The delivery of nanomedicine to the bloodstream exposes the cardiovascular system to a potential threat. However, the possible adverse cardiovascular effects of HANPs remain unclear. Current observations using coculture models of endothelial cells and monocytes with HANPs to mimic the complex physiological functionality of the vascular system demonstrate that monocytes could play an important role in the mechanisms of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…In contrast, the HUVEC layer treated with PBS or IO@NP-pD-Al showed much smaller vesicles (0.07 – 0.2 μm) resembling caveolae [54]. Although individual NPs could not be identified, the large vesicles in IO@NPxAl-treated HUVEC are thought to be lysosomes filled with IO@NPxAl, given the morphological similarity to the lysosomes seen in HUVEC internalizing metal and silica particles [55, 56]. The NP content in the HUVEC layer and the TEM image indicate that a greater fraction of NPxAl was stuck in HUVEC during the transport across the cell layer as compared to NP-pD-Al.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the HUVEC layer treated with PBS or IO@NP-pD-Al showed much smaller vesicles (0.07 – 0.2 μm) resembling caveolae [54]. Although individual NPs could not be identified, the large vesicles in IO@NPxAl-treated HUVEC are thought to be lysosomes filled with IO@NPxAl, given the morphological similarity to the lysosomes seen in HUVEC internalizing metal and silica particles [55, 56]. The NP content in the HUVEC layer and the TEM image indicate that a greater fraction of NPxAl was stuck in HUVEC during the transport across the cell layer as compared to NP-pD-Al.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have postulated that interactions of cells with surfaces of HA particles are mediated by integrins on cell membranes[77,78]. HA particle uptake has been shown to induce activation in endothelial cells, with increased IL-6 production[79], as well as induction of osteogenic differentiation in human adipose-derived stem cells[80]. Additionally, it has been established that crystals of a differing size can affect cellular response[81].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from previous studies showed that nanoparticles can activate mitogen-activated protein kinase (MAPK) signaling cascade 7 in cells which include macrophages, 8 bone marrow stromal cells (BMSCs), 13 and endothelial cells (ECs). 14 We hypothesized that extracellular nHAp stimulated MAPK pathways which caused gene expression changes in SMCs. We found that JNK/c-JUN signaling pathway is critical for nHAp-induced VC.…”
Section: Introductionmentioning
confidence: 99%